PRUDENCE MANAGEMENT OF LOCAL GOVERNMENT COMPANY - Muchamad Taufiq; Agus Salim (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2020)
The existence of  local government companies which is strategic with the task of serving the public needs and the realization of welfare must be managed properly and correctly. In order to realize a good and right management must begin with prudence. The formulation of the problem of this research is what is the philosophical basis of prudence and how is the application of prudence in local government companies. This study aims to examine, analyze, understand and explain the prudential philosophical basis and discover as well as to explain the prudential concept in management of local government companies. Benefits of this research are theoretically expected to provide study, analysis, understanding and the explanation of the basic philosophical prudential and practically useful in finding and explaining the concept of prudence in the management of  local government companies. This type of research is a normative juridical review as the characteristic of law which is " Sui Generis ".